The application of multi-grounded source transient electromagnetic method in the detections of coal seam goafs in Gansu Province, China. (9th August 2021) - Lu, Kailiang; Li, Xiu; Fan, Ya'nan; Zhou, Jianmei; Qi, Zhipeng; Li, Wenhan; Li, He
Abstract: Unknown coal seam goafs will pose various safety hazards in construction and engineering designs, thus the accurate detections of coal seam goafs have become engineering problems that urgently require effective solutions. Multi-grounded source transient electromagnetic methods have the advantages of large detection depths and the easy deployment of emission sources. Therefore, they can be used for explorations in such complex areas as mountains, lakes and swamps. Previously, grounded source transient electromagnetic methods had only one emission source arranged on the surface, and were relatively rarely used in field explorations with multi-grounded sources. This study analyses the electromagnetic response differences between multi-grounded sources and a single-grounded source. The results reveal that the electromagnetic responses of multi-grounded sources were larger. Transient electromagnetic signals were be targeted using combinations of multi-grounded sources, which successfully strengthened the detection abilities. As a result, this study was able to achieve the goals of increasing the detection depths and improving the ability to distinguish geological anomalies. In addition, this research investigation referred to the theory of implicit functions and used the z components of the decay voltage to calculate the apparent resistivity. Finally, the results of the field data of a coal goaf located in Gansu Province, China, showed that the applied multi-grounded sources transient electromagnetic method could obtain higher resolution in coal seam goaf resistivity distribution information.